New forms of anticance drugs «Arglabin» based on human serum albumin - Burkeev, M.Zh.; Kreuter, J.; Tazhbayev, Ye.M.; Kazhmuratova, A.T.; Zhaparova, L.Zh.; Zhumagalieva, T.S.; Muhanova, D.A. (Вестник Карагандинского университета, 2016)
In this article the possibility of creation of human serum albumin nanoparticles immobiized by anticancer drug Arglabin was considered. Physical and chemical charasterictics of nanoparticles and binding of Arglabin with polymeric nanoparticles were determined It is found that the particle size and binding of drug with polfymer depend on the method of immobilization of drug.
Keywords: albumin; nanoparticles; immobilization; Arglabin; polydispersity; zetapotential